PENATALAKSANAAN SINDROMA MAYER ROKITANSKY KUSTER HAUSER (SINDROMA MRKH) DENGAN SINDROMA KLIPPEL FEIL - Wiyasa IW, Arsana; Mukminah, Aisyatul (Jurnal Kedokteran Brawijaya, 2004)
ABSTRACT It was reported that a 19 year old woman, suffered from Muller duct agenesis. The patient came to RSSA, complained about primary amenorrhea and assimetrical of head position. Tuba, uterus and 2/3 proximal vagina were not formed. Both of ovaries seemed normal. Based on vaginal sondage, the vagina canal is only 1.5 cm. Secondary sexual characteristics developed normally. By skull and cervical X – ray, it was found fusion of vertebrae cervical 3, 4. The vagina and the uterus are not present, but the tuba and the ovarium are normal; this case is known as Mayer Rokitansky Kuster Hauser Syndrome. Moreover, it is accompanied by another congenital defect, i.e. fusion of vertebrae cervical 3 and 4, which is called Klippel Feil Syndrome. In the exploration, it was found that there was a constitution of cromosom 46,XX. It has been done hormonal examination: FSH, LH, estrogen, prolactin and was obtained testosteron < 127.8 ng/dl. The patient was grews up as a woman. Her behavior, attitude, emotion and sexual behavior are likely a woman.  We plan to perform and suggest her to adopts a child. To treat the Klippel Feil, it is important prevention of the neck trauma and complication of neurology and arthritis. Key word : Mayer Rokitansky Kuster Hauster Syndrome, Klippel Feil Syndrome, vaginoplasty